Cognitive Level of Chromebook-Based Summative Assessment Questions on The Independent Curriculum in Driving Schools - Rubingah, Nurur; Sutopo, Anam; Wulandari, Murfiah Dewi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This study aims to describe the cognitive level of chromebook-based summative assessment questions in the Merdeka Curriculum in driving schools. This research is a qualitative study using textual data analysis. The data source in this study is chromebook-based summative assessment items on the independent curriculum at the driving school. The results of the research obtained are Chromebook-based summative assessment questions on the independent curriculum in driving schools that do not contain all levels of the cognitive process dimension, because there are no questions with the C5-Evaluation level and the C6-Creating level. The questions are still dominated by the C2-Understanding level which can be categorized as LOTS (Lower Order Thingking Skills). This has an impact on the lack of students' critical thinking skills.